Improving prediction models applied in systems monitoring natural hazards and machinery - Sikora, Marek; Sikora, Barbara (Zielona Góra: Uniwersytet Zielonogórski)
A method of combining three analytic techniques including regression rule induction, the k-nearest neighbors method and time series forecasting by means of the ARIMA methodology is presented. A decrease in the forecasting error while solving problems that concern natural hazards and machinery monitoring in coal mines was the main objective of the combined application of these techniques. The M5 algorithm was applied as a basic method of developing prediction models.
Keywords: natural hazards monitoring; regression rules; time series forecasting; k-nearest neighbors